مساهمة المحاسبة البيئية في تحقيق التنمية المستدامة - (:unkn) unknown (University of Eloued جامعة الوادي, 2019)
تهدف الدراسة إلى الوقوف على وصف المحاسبة البيئية وتحديد أثر القياس والإفصاح عن الأداء البيئي للمؤسسات في ظل الاهتمام المتزايد بقضايا البيئية والتنمية المستدامة اللذان تربطهما علاقة تكاملية تسعى إلى إحداث التوازن بين النظام البيئي والنظام الاقتصادي من خلال ترشيد قرارات الوحدات الاقتصادية وتوجيهها نحو بناء نظام للإدارة البيئية يقلل من استنزاف الموارد البيئية المتجددة والغير المتجددة من النفاذ ويضمن حق الأجيال القادمة، ولأجل معالجة الموضوع تم استخدام المنهج الوصفي الذي استخرجت منه العديد من النتائج أهمها أن الإفصاح البيئي يؤدي إلى ترشيد القرارات والمحافظة على النظام البيئي. Abstract: The study aims to identify the description of environmental accounting and determine the impact of measurement and disclosure of environmental performance of institutions in light of the growing interest in environmental issues and sustainable development which have an integrated relationship that seeks to strike a balance between the ecosystem and the economic system by rationalizing the decisions of economic units and directing them towards building an environmental management system that reduces the depletion of renewable and non-renewable environmental resources from access and guarantees the right of future generations, and in order to address the subject a descriptive approach was used from which many conclusions were drawn, the most important of which is that environmental disclosure leads to the rationalization of decisions and the preservation of the ecosystem.
Contribution of environmental accounting to sustainable development realization
الملتقى الدولي الثامن حول: الاتجاهات الحديثة للتجارة الدولية وتحديات التنمية المستدامة نحو رؤى مستقبلية واعدة للدول النامية 02/ 03 ديسمبر 2019 - كلية العلوم الاقتصادية والتجارية وعلوم التسيير - جامعة الشهيد حمه لخضر - الوادي
Keywords: المحاسبة البيئية، التنمية المستدامة،الأداء البيئي. تصنيف JEL : E ؛ E0 ؛ E02; environmental accounting, sustainable development, environmental performance Jel Classification Codes : E; E0; E02